Computational Tools for Discovering and Engineering Natural Product Biosynthetic Pathways - Ren, Hengqian; Shi, Chengyou; Zhao, Huimin (iScience, 2020)
Natural products (NPs), also known as secondary metabolites, are produced in bacteria, fungi, and plants. NPs represent a rich source of antibacterial, antifungal, and anticancer agents. Recent advances in DNA sequencing technologies and bioinformatics unveiled nature's great potential for synthesizing numerous NPs that may confer unprecedented structural and biological features. However, discovering novel bioactive NPs by genome mining remains a challenge. Moreover, even with interesting bioactivity, the low productivity of many NPs significantly limits their practical applications. Here we discuss the progress in developing bioinformatics tools for efficient discovery of bioactive NPs. In addition, we highlight computational methods for optimizing the productivity of NPs of pharmaceutical importance. [Display omitted] Biological Sciences; Bioengineering; Metabolic Engineering; Bioinformatics